Салтово-маяцкие комплексы поселения Осовины-I - Зинько, В.Н.; Пономарев, Л.Ю. (Материалы по археологии, истории и этнографии Таврии, 2007)
Салтово-маяцкие памятники северо-восточной оконечности Керченского полуострова привлекли внимание исследователей только в послевоенные годы, когда на археологическую карту их впервые нанес инженер и археолог-любитель В.В. Веселов. Часть из них находилась на побережье Керченского пролива и на берегу Азовского моря. Девять поселений обнаружены В.В. Веселовым у пос. Подмаячное, два - у пос. Глейки, пять - у с. Осовины и три - у с. Юркино. Поселение Осовины-1 расположено на побережье Азовского моря в 0,5 км к западу от мыса Варзовка (Барзовка) и в 1,4 км к юго-востоку от с. Осовины. In 1950, on the shore of the Sea of Azov, to the south-west from the settlement of Osovini, on the Kerch peninsula, V. V. Veselov discovered a multi-layer settlement of Osovini- I. During the excavations undertaken here in 1989-1933 it was ascertained that after the ruin of the settlement in the mid-3rd century AD, in the 8th - the first half of the 10th centuries there was a Saltovo-Mayatzki settlement on Its territory. A two-chamber house (SK-A) built in the first centuries AD was accommodated by inhabitants as one of the dwellings. After reconstruction, having the same planning, it was used in accordance with its purpose. This building vividly demonstrates one of the mechanisms of getting acquainted with a principally new type of dwelling for the Turks-Bulgarians. Next to the SK-A a small early-medieval cemetery was discovered where three ground graves were investigated. The state of skeletons shows that the funeral rite of neutralizing the dead was performed. Remove selected